EXPLORING INNOVATIVE QURANIC TECHNOLOGIES IN EARLY CHILDHOOD EDUCATION: TRENDS ANALYSIS - Salleh, Khadijah Aini; Abd Hamid, Samsuddin; Yusoff, Tarmizi; Salleh, Rashidah; Anuar, Nur Liyana Athirah (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study explores global research trends and innovative technological applications related to Quranic education in early childhood settings. With the increasing integration of digital tools in religious instruction, especially in early education, there is a growing need to understand how Quranic pedagogy is evolving through technological innovations. Despite the rapid advancement of educational technologies, limited bibliometric analyses have focused specifically on Quranic technologies within early childhood education. This gap presents a critical opportunity to map the development, frequency, and direction of scholarly work in this niche domain. The objective of this research is to systematically analyze published literature from 2020 to 2024 using bibliometric techniques to uncover patterns, influential authors, key institutions, core keywords, and prevailing themes in the field. The methodology involved retrieving relevant documents from the Scopus database using refined keyword searches. Data cleaning was performed using OpenRefine to ensure consistency and accuracy in author names, affiliations, and publication sources. VOSviewer was then used to visualize co-authorship networks, keyword co-occurrence, and citation mapping. The final dataset consisted of 1,425 documents, revealing a steady increase in publications over the last five years, with a concentration of contributions from Southeast Asia and the Middle East. Keywords such as “Quranic learning,” “early childhood education,” and “educational technology” were among the most frequently occurring terms. The analysis also highlighted a strong emphasis on digital platforms, gamification, and AI-supported learning tools in contemporary Quranic instruction. In conclusion, this bibliometric analysis provides valuable insights into the evolving landscape of Quranic technologies in early childhood education, serving as a foundational reference for future interdisciplinary research and practical implementation in Islamic pedagogical contexts.